Sun Block Technique In Indigosol Dyeing For Textile Artwork - Djandjang Purwo Sedjati; Hidayatun Nurfiani (Institut Seni Indonesia Yogyakarta, 2022)
Indigosol is one of the chemical color substances widely used in textile coloring through coletan (brushing) or celupan (dipping) to result in bright color. The coloring process requires the sun's ultraviolet rays. Early observations about the process of coloring fabric with indigosol indicate the importance of using the gap in the heating process with the sun as a new technique in decorating the fabric. It is assumed that when the radiation process occurs, if there is something attached to the fabric exposed to the sun, then the indigosol dye can not appear because it is blocked by an object so that the part attached to an object maintains the original color. The process of heating with the sun in indigosol dyeing technique is a diversification technique or transfer of function in fabric decoration. This study employs the library and observation methods to collect data. The practice-led research method is used to create and reflect on new work. The method focuses on the practice of scientifically written creation processes. Experimental methods are carried out mainly on the indigosol dyeing process combined with remazol and batik techniques. Improvisation is made in cultivation to find new ideas to create works. In applying indigosol, the coloring techniques will be done with blocks using such unique and artistic objects as flora, especially leaves and flowers, and such materials as brocade, tule, or terawang woven combined with remazol color. In addition, dyes will also be involved in batik techniques. The works are all functional and made in silk and cotton sheets. Six types of works are made with engineering techniques obtained from the results of experiments.